Virulence traits, agr typing, multidrug resistance patterns, and biofilm ability of MDR Staphylococcus aureus recovered from clinical and subclinical mastitis in dairy cows - Nada H. Eidaroos; Abdelazeem M. Algammal; Walaa Ismail Mohamaden; Asma Massad Alenzi; Saad Alghamdi; Ahmed Kabrah; Heba Sayed El-Mahallawy; Hamza M. Eid; Alaa Abd Algwad; Samar Ali Asfor; Heinrich Neubauer; Amira A. Moawad; et al. (BMC Microbiology)
Abstract Background Bovine mastitis caused by Staphylococcus aureus is considered a public health threat globally. Herein, we aimed to investigate the occurrence, agr typing, antimicrobial resistance patterns, biofilm production, and PCR-based detection of the virulence, biofilm, adhesion, and enterotoxins genes of S. aureus strains recovered from clinical and subclinical bovine mastitis. Results The prevalence of S. aureus in the examined milk samples was 44.4%. Besides, 95% of the retrieved S. aureus strains were identified as MRSA. Herein, all the tested isolates were biofilm producers. PCR revealed that 85% of the retrieved S. aureus strains were positive for the agr I gene. Furthermore, the clfB, clfA, fnbB, fnbA, and cna genes were detected with a prevalence of 100%, 80%, 60%, 55%, and 30%, respectively. Also, all the tested S. aureus strains were positive for the coa gene (100%). Besides, 92.5% and 85% of the recovered strains harbored the lukF and spa genes, respectively. In addition, the prevalence of the hla, hlb, and hlg hemolysin genes was 70%, 50%, and 35%, respectively. Among the enterotoxin genes, the seb gene was detected in 30% of the tested strains. The prevalence of eno and icaA biofilm genes was 95% in the tested strains. Moreover, 15% of S. aureus strains were MDR to 8 antimicrobial agents and harbored the mecA, ermC, and ermB genes. As well, 12.5% of S. aureus strains were MDR to 8 antimicrobial agents and carried the mecA, ermC, ermB, tetK, and tetM genes. Also, 5% of S. aureus strains were XDR to 11 antimicrobial agents and carried the mecA, ermC, and ermB genes. Conclusions The existence of MDR and XDR MRSA strains in bovine milk is a public health hazard. The mecA, ermC, ermB, tetK, and tetM resistance genes and the coa, clfB, eno, icaA, lukF, spa, clfA, and hla virulence genes are commonly associated with the MDR and XDR MRSA strains. Moreover, the seb gene was the predominant enterotoxin gene in the MRSA strains recovered from milk.